Validity of the Ekblom-Bak Cycle Ergometer Test in Patients with Cardiovascular Disease - Magnus Fransplass Storli; Marius Steiro Fimland; Harald Kåre Engan; Jon Arne Sandmæl (Medical Journals Sweden, 2024)
Objective: To assess the validity of the Ekblom-Bak cycle ergometer test in patients with cardiovascular disease admitted to cardiac rehabilitation. Methods: Estimated peak oxygen consumption from the Ekblom-Bak test was compared with directly measured peak oxygen consumption from a treadmill cardiopulmonary exercise test. Patients completed the cardiopulmonary exercise test first, followed by the Ekblom-Bak test after 24 h rest. Pearson's correlation coefficient (r) was used to establish the correlation between estimated and measured peak oxygen consumption, and Bland-Altman plots with limits of agreement were used to determine the bias between the 2 tests. Results: Twenty-six patients were included in the final analysis. The Ekblom-Bak test significantly overestimated peak oxygen consumption. Agreement between estimated and measured peak oxygen consumption was: bias = 4.3 mL/kg/min (limits of agreement: -4.0-12.6 mL/kg/min). Conclusion: The Ekblom-Bak test overestimated peak oxygen consumption to such an extent that it cannot accurately assess cardiorespiratory fitness in patients with cardiovascular disease. Thus, the cardiopulmonary exercise test remains the test of choice.